Karma Yoga as a Coping Mechanism for Anxiety - Tanya Goel; Rita Kumar; Sheetal Mehrotra (International Journal of Behavioral Sciences, 2024)
This Research article aims to investigate the effectiveness of Karma Yoga as a coping mechanism for anxiety. Karma yoga, an ancient spiritual practice originating from the teachings of the Bhagavad Gita, promotes service and selfless action devoid of expectations and fear of its result. In the Bhagavad Gita, Lord Krishna advises individuals to perform their duties without fear of its result. “Any action which is performed by a living entity using the mind, body and senses with awareness and consciousness is known as karma”. Action done without the involvement of ego or attachment becomes yoga of action which is known as Karma Yoga. Anxiety, as defined by the American Psychological Association, is an emotion characterized by feelings of tension, worry, and physiological changes such as increased heart rate. Discrepancies between planned and actual outcomes heighten our apprehension and increase anxiety. For the purpose of this study, a review of 20 research papers was conducted which suggests that the practice of karma yoga reduces anxiety. Additionally, it promotes mental clarity and emotional resilience, which makes it easier for people to deal with life's obstacles. This implies that integrating the principles of Karma Yoga into daily routine can serve as a valuable tool for managing and coping with anxiety symptoms
Keywords: Anxiety; coping mechanism; karma yoga; selfless actions; stress management